Developing effective interorganizational relationships between community corrections and community treatment providers. Issue 7 (2nd October 2016) - Monico, Laura B.; Mitchell, Shannon Gwin; Welsh, Wayne; Link, Nathan; Hamilton, Leah; Malvini Redden, Shawna; Schwartz, Robert P.; Friedmann, Peter D.
ABSTRACT: Weak service coordination between community corrections and community treatment agencies is a significant barrier in the diffusion of pharmacotherapy for treating opioid and alcohol use disorders. This analysis draws on qualitative interviews ( n  = 141) collected in a multisite randomized trial to explore what probation/parole officers and treatment staff believe are the most critical influences on developing positive interorganizational relationships between their respective agencies. Officers and treatment staff highlighted factors at both the individual and organizational level, with issues related to communication surfacing as pivotal. Findings suggest that future interventions consider developing shared interagency goals with input at all staff levels.